The Impact of PNF Stretching on Pain and Range of Motion Compared to Static Stretching in Patients with Piriformis Syndrome: A Randomized Controlled Trial - J, Mahendran; Selvaganapathy, Karthikeyan; M, Kamalakannan; Rajappan, Roshini; Abudaheer K, Syed (Journal of Neonatal Surgery, 2025)
Introduction: Piriformis syndrome is a neuromuscular disorder causing pain and restricted mobility. Proprioceptive Neuromuscular Facilitation (PNF) stretching is a technique used to improve muscle elasticity and range of motion (ROM), but its effectiveness in piriformis syndrome remains underexplored. Objective: This study investigates the effectiveness of PNF stretching in alleviating pain and enhancing ROM in patients with piriformis syndrome. Method: A randomized controlled trial with 30 participants (53.3% male, mean age45 ) was conducted. Both groups underwent a 4-week intervention comprising hot pack application, manual therapy, and stretching protocols. Pain levels were measured using the Visual Analogue Scale (VAS), and ROM was assessed with a goniometer. Results: The experimental group showed significant improvements in ROM (extension: 110 ± 30; abduction: 310 ± 70; external rotation: 300 ± 60) and pain reduction (VAS: 5 ± 2) compared to the control group. Statistical analysis demonstrated greater significance for PNF stretching in improving ROM and pain reduction compared to static stretching. Conclusion: PNF stretching significantly enhances ROM and reduces pain in piriformis syndrome patients, offering a promising rehabilitation strategy. Future studies should explore long-term benefits and variations in PNF protocols.